Overall Job Satisfaction: Case Study in Penang Development Cooperation (PDC) - Mohammad Adha, Amin (2010)
The aim of this study was to investigate and describe the job satisfaction of a sample of Penang Development Cooperation (PDC) workers. This study was meddled as a replication study, where data would be collected through the use of the validated and widely tested Minnesota Satisfaction Questionnaire (MSQ). This study had attempted to document overall job satisfaction levels and to report the findings of 20 individual subscales, of the MSQ that examined the sources of job satisfaction. The intended sample was PDC workers, the PDC is the state economic development corporation which serves the State of Penang in Malaysia. A total of 83 questionnaires were distributed on a 2 weeks focusing on the PDC workers. From this 58 questionnaires were received back giving the study a 70 percent response rate. This study could not conclusively determined whether the sampled respondent were satisfied or less satisfied with their jobs. The result mean scores of the MSQ scales only indicated that the respondents were satisfied with only five dimensions it is pay, promotion, supervision, coworker and satisfaction with the work itself (out of 20 MSQ dimensions). The dimensions were related to intrinsic dimensions - being able to do things on the job that did not go against their conscience (mean score=3.76) and the way the job provides for steady employment (mean score=3.76). Another finding was that the respondents were more satisfied with intrinsic job satisfaction dimensions than with extrinsic job satisfaction.